Effect of seed hydro-priming durations on germination and seedling growth of bitter gourd (Momordica charantia) - Binod Adhikari; Pankaj Raj Dhital; Sambat Ranabhat; Hari Poudel (PLoS ONE, 2021)
The yield and quality of an annual crop are highly dependent on uniform and rapid germination of the seeds. In case of bitter gourd (Momordica charantia), the germination and field emergence is always a problem as seeds have thick and hard seed coat. Pre-sowing hydro-priming is one of the most suitable, affordable, easily available, and cost-effective techniques in breaking down seed dormancy to enhance germination. Hence, a field experiment was conducted in Surkhet district of Nepal 2020 to assess the effect of different hydro-priming duration on germination and seedling growth of bitter gourd. The experiment was laid out in single factor Randomized Complete Block Design (RCBD) with four replications and seven treatments including different hydro-priming durations (T0: control, T1: 6 hours, T2: 12 hours, T3: 18 hours, T4: 24 hours, T5: 36 hours and T6: 48 hours) of bitter gourd seeds of Palee variety, the most popular variety among the farmers. The highest water uptake and germination were found in 48 hours of seed hydro-primed seeds whereas the lowest water uptake and germination were observed on non-primed seeds. Similarly, the tallest seedling, most vigorous seedling in terms of seedling vigour index I and II was observed in 48 hours hydro-primed seeds followed by 36 hours of seed hydro-priming and shortest seedling and the least vigorous seedling in control. Thus 48 hours of seed hydro-priming was found to be effective for increasing germination and seedling growth in bitter gourd, which needs to be further investigated under large, open-field conditions with different varieties.